peranan e-book sains terhadap minat belajar - Sheilla Fallerina Meydi; Elsa Indah Laksamana; Arinda Maharani; Jennis Ayu Wulandari; I Ketut Mahardika; Singgih Bektiarso (Peneliti.net, 2023)
Science is the ability to understand science, communicate science, and apply scientific abilities to solve problems. This research aims to determine the interest of students in learning using science E-book media. There are two factors that influence the success of the learning process, two of which are teaching methods and learning media. The method used in this research is to search and select articles related to the topics that have been determined, perform analysis, and draw a conclusion from a collection of articles reviewed. Media in an educational perspective is an influential instrument in determining the results of the learning process. The use of learning media using science e-books as an effort to increase students' interest in learning about science or science.